PERSPEKTIF YURIDIS DAN ETIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 2/PUU-XX/2022 - Munawwar, Said (Universitas Muhammadiyah Ponorogo, 2024)
The decision of the Constitutional Court Number 2/PUU-XX/2022 sparked an interesting theoretical debate. This decision provides space for former narcotics convicts to run in regional head elections. According to the Constitutional Court, the decision